2013
DOI: 10.1177/1524839913485757
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Among Asian Americans

Abstract: New York City (NYC) has experienced significant decline in smoking prevalence since its antismoking campaign; however, the rates among NYC’s Asian communities have persisted since 2002. Using combined data from the REACH US Risk Factor Survey (2009-2011), this article examined ethnic- and gender-specific smoking behaviors and the effects of acculturation and location of residence on cigarette smoking behavior among Chinese, Korean, Asian Indians, and other Asian Americans. Results indicated that current smokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 30 publications
3
37
0
Order By: Relevance
“…Smoking prevalence (7.4%) was similar to overall smoking rates among older respondents in NYC (8.2%) (New York City Department of Health and Mental Hygiene, 2012); however, 14.8% of men and 1.3% of women were current smokers, and 33.8% of men and 3.8% of women were former smokers, similar to previous studies (Li, Kwon, Weerasinghe, Rey, & Trinh-Shevrin, 2013; Maxwell, Bernaards, & McCarthy, 2005; Yu, Chen, Kim, & Abdulrahim, 2002). As shown previously, lower educational attainment is associated with current smoking among men (Parikh et al, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…Smoking prevalence (7.4%) was similar to overall smoking rates among older respondents in NYC (8.2%) (New York City Department of Health and Mental Hygiene, 2012); however, 14.8% of men and 1.3% of women were current smokers, and 33.8% of men and 3.8% of women were former smokers, similar to previous studies (Li, Kwon, Weerasinghe, Rey, & Trinh-Shevrin, 2013; Maxwell, Bernaards, & McCarthy, 2005; Yu, Chen, Kim, & Abdulrahim, 2002). As shown previously, lower educational attainment is associated with current smoking among men (Parikh et al, 2009).…”
Section: Discussionsupporting
confidence: 86%
“…(See Table 1. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] ) All papers were reviewed by one author (CG) and by one or more of the other authors, with coding disagreements resolved through discussion. Papers were reviewed against the STROBE Statement 22-item checklist for cross-sectional studies 33 to ensure they were adequately reported.…”
Section: Methodsmentioning
confidence: 99%
“…Five of the eight studies that used some aspect of language use or proficiency as an indicator of acculturation found a relationship 19,21,23,27,32 and three did not, 25,26,28 such that more use of English language was linked with less smoking for men 19,22,24,28,30,32 Both studies that distinguished between foreign-and North American-born found a relationship with smoking behaviour, 19,27 such that men born in China smoked more 27 and women born in China smoked less. 19,27 Of the studies that used multidimensional acculturation scales, 20,29,31,32 two studies, both in adolescents, did not find a relationship between scale scores and acculturation. 20,31 Among adults, one study found that the acculturation scale was associated with smoking for females, with more smoking among more acculturated women, but in men, the only significant factor that predicted smoking was earlier age at immigration.…”
Section: Smoking Prevalencementioning
confidence: 97%
See 1 more Smart Citation
“…3 Lower acculturation and limited English proficiency (LEP), the latter defined by self-rated spoken English proficiency as less than well, 4 are associated with higher smoking and lower quit rates. 5,6 While the current smoking prevalence rate among non-Hispanic white males is 21%, 7 recent immigrant or LEP Chinese and Vietnamese men have disproportionately high rates, ranging from 22% to 34% for Chinese men [8][9][10][11] and 25% to 37% for Vietnamese men. [12][13][14] Among LEP immigrants, Vietnamese men (43%) and Chinese men (32%) had the highest and the second highest smoking prevalence rates, respectively, among all Asian subgroups in California.…”
Section: Introductionmentioning
confidence: 99%